2010
DOI: 10.1177/1757913910369090
|View full text |Cite
|
Sign up to set email alerts
|

Benefits arising from lay involvement in community-based public health initiatives: The experience from community nutrition

Abstract: Aims: To explore the experiences of lay food and health workers (LFHW) and professionals involved in delivering local food and health initiatives, to improve understanding of the perceived benefits associated with their involvement and wider opportunities for promoting health. Study design: An interpretive qualitative inquiry. Setting: Community-based NHS LFHW programmes in 16 locations serving less-affluent neighbourhoods across England, UK. Subjects: Twenty nine (29) food and health professionals, 53 LFHW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Boundary spanning to improve performance and uptake of health services was used to increase participation rates in clinical services [ 39 42 , 45 , 48 , 49 , 52 , 63 ] or to achieve a change in health behaviours and outcomes [ 27 , 44 , 47 , 51 , 53 , 55 , 58 61 ]. In the former, boundary spanners have a stronger organisational orientation, and in the latter, health services use boundary spanners because of their community orientation.…”
Section: Resultsmentioning
confidence: 99%
“…Boundary spanning to improve performance and uptake of health services was used to increase participation rates in clinical services [ 39 42 , 45 , 48 , 49 , 52 , 63 ] or to achieve a change in health behaviours and outcomes [ 27 , 44 , 47 , 51 , 53 , 55 , 58 61 ]. In the former, boundary spanners have a stronger organisational orientation, and in the latter, health services use boundary spanners because of their community orientation.…”
Section: Resultsmentioning
confidence: 99%
“…They constitute an untapped resource whose potential has been evidenced in the USA. Kennedy and colleagues 314,315 have explored the benefits arising from lay involvement in community-based nutrition programmes in poor neighbourhoods. These include increased service coverage and the ability to reach populations, personal development and enhanced social support.…”
Section: Community Participationmentioning
confidence: 99%
“…[310][311][312][313][314][315] For example, Daykin and Naidoo 310 explored the views of health professionals on promoting health in areas of poverty with low-income clients. They questioned the assumption that primary health care is the best setting for health promotion; several constraints are identified as limiting its effectiveness.…”
Section: Community Participationmentioning
confidence: 99%
“…Prior work has shown that TB health education can be effective if health promotion practitioners create a supportive environment and understand the cultural barriers [8]. The use of community lay workers is vital at increasing screening coverage and reaching the hard to reach black communities [27]. Community-based programs help people become active participants in improving their health and wellbeing, rather than acting as passive recipients of professional efforts [28].…”
Section: Discussionmentioning
confidence: 99%